2012
DOI: 10.1371/journal.pone.0033092
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Avian Influenza in Tree Sparrows in China in 2011

Abstract: Tree sparrows ( Passer montanus ) are widely distributed in all seasons in many countries. In this study, a survey and relevant experiments on avian influenza (AI) in tree sparrows were conducted. The results suggested that the receptor for avian influenza viruses (AIVs), SAα2,3Gal, is abundant in the respiratory tract of tree sparrows, and most of the tree sparrows infected experimentally with two H5 subtype highly pathogenic avian influenza (HPAI) viruses died within five days after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Despite this apparent geographic restriction, clade 1. (19)(20)(21)(22)(23)(24). Despite their detection in 37 of 63 provinces in Vietnam, the clade 2.3.2.1c viruses showed limited diversity, suggesting that they originated from a single progenitor source.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this apparent geographic restriction, clade 1. (19)(20)(21)(22)(23)(24). Despite their detection in 37 of 63 provinces in Vietnam, the clade 2.3.2.1c viruses showed limited diversity, suggesting that they originated from a single progenitor source.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports documented that influenza A viruses, including subtypes H5N1 and H3N2, have been isolated from sparrows ( 11 , 12 ). A serologic survey also suggested that rates of influenza A virus infection were high among sparrows ( 13 ), which might result from abundant distribution of avian influenza virus receptor SA α2,3Gal in the respiratory tracts of sparrows ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…65 Infl uenza A subtypes H7N1, H7N2, H7N3, H7N7, and H7N8 were previously isolated from poultry and wild birds from China. 38,66 Although studies of seroprevalence did not fi nd any evidence of H7 infection among sparrows or pigs in China, 67,68 H7N9 viruses were isolated from birds in nearby countries, including Mongolia and South Korea in 2008. 69,70 Moreover, in the USA, H7N9 viruses have caused outbreaks in chickens.…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%